Cleaning and disinfecting surfaces in hospitals and long-term care facilities for reducing hospital- and facility-acquired bacterial and viral infections: a systematic review. (April 2022) - Thomas, R.E.; Thomas, B.C.; Conly, J.; Lorenzetti, D.
Summary: Background: Multiply drug-resistant organisms (MDROs) in hospitals and long-term care facilities (LTCFs) of particular concern include meticillin-resistant S taphylococcus aureus (MRSA), vancomycin-resistant enterococcus, multidrug-resistant Acinetobacter species, and extended-spectrum β-lactamase-producing organisms. Respiratory viruses include influenza and SARS-CoV-2 . Aim: To assess effectiveness of cleaning and disinfecting surfaces in hospitals and LTCFs. Methods: CINAHL, Cochrane CENTRAL Register of Controlled Trials, Embase, Medline, and Scopus searched inception to June 28 th, 2021, no language restrictions, for randomized controlled trials (RCTs), cleaning, disinfection, hospitals, LTCFs. Abstracts and titles were assessed and data abstracted independently by two authors. Findings: Of 14 cluster (c)-RCTs in hospitals and LTCFs, interventions in ten were focused on reducing patient infections of four MDROs and/or healthcare-associated infections (HAIs). In four c-RCTs patient MDRO and/or HAI rates were significantly reduced with cleaning and disinfection strategies including bleach-, quaternary ammonium detergent-, ultraviolet irradiation-, hydrogen peroxide vapour- and copper-treated surfaces or fabrics. Of three c-RCTs focused on reducing MRSA rates, one had significant results and one on Clostridioides difficile had no significant results. Heterogeneity of populations, methods, outcomes and data reporting precluded meta-analysis. Overall risk of bias assessment was low but high for allocation concealment, and GRADE assessment was low risk. No study assessed biofilms. Conclusion: Ten c-RCTs focused on reducing multiple MDROs and/or HAIs and four had significant reductions. Three c-RCTs reported only patient MRSA colonization rates (one significant reductions), and one focused on C. difficile (no significant differences). Standardized primary and secondary outcomes are required for future c-RCTs including detailed biofilm cleaning/disinfection interventions.